Endothelium-Derived 5-Methoxytryptophan Is a Circulating Anti-Inflammatory Molecule That Blocks Systemic Inflammation. Issue 2 (8th July 2016) - Wang, Yi-Fu; Hsu, Yu-Juei; Wu, Hsu-Feng; Lee, Guan-Lin; Yang, Ya-Sung; Wu, Jing-Yiing; Yet, Shaw-Fang; Wu, Kenneth K.; Kuo, Cheng-Chin
Abstract : Rationale: : Systemic inflammation has emerged as a key pathophysiological process that induces multiorgan injury and causes serious human diseases. Endothelium is critical in maintaining cellular and inflammatory homeostasis, controlling systemic inflammation, and progression of inflammatory diseases. We postulated that endothelium produces and releases endogenous soluble factors to modulate inflammatory responses and protect against systemic inflammation. Objective: : To identify endothelial cell–released soluble factors that protect against endothelial barrier dysfunction and systemic inflammation. Methods and Results: : We found that conditioned medium of endothelial cells inhibited cyclooxgenase-2 and interleukin-6 expression in macrophages stimulated with lipopolysaccharide. Analysis of conditioned medium extracts by liquid chromatography–mass spectrometry showed the presence of 5-methoxytryptophan (5-MTP), but not other related tryptophan metabolites. Furthermore, endothelial cell–derived 5-MTP suppressed lipopolysaccharide-induced inflammatory responses and signaling in macrophages and endotoxemic lung tissues. Lipopolysaccharide suppressed 5-MTP level in endothelial cell-conditioned medium and reduced serum 5-MTP level in the murine sepsis model. Intraperitoneal injection of 5-MTP restored serum 5-MTP accompanied by the inhibition of lipopolysaccharide-induced endothelial leakage and suppression of lipopolysaccharide- or cecal ligation and puncture–mediated proinflammatory mediators overexpression. 5-MTP administration rescued lungs from lipopolysaccharide-induced damages and prevented sepsis-related mortality. Importantly, compared with healthy subjects, serum 5-MTP level in septic patients was decreased by 65%, indicating an important clinical relevance. Conclusions: : We conclude that 5-MTP belongs to a novel class of endothelium-derived protective molecules that defend against endothelial barrier dysfunction and excessive systemic inflammatory responses. Abstract : Supplemental Digital Content is available in the text.